Lessons Learned from the Forest, Climate and Communities Alliance - and Boshoven, Judy (USAID, 2014)
The Forest, Climate, and Communities Alliance (FCCA) was an initiative funded by USAID’s Bureau for Economic Growth, Education, and the Environment/Office of Forestry and Biodiversity (E3/FAB) under the USAID Global Development Alliance (GDA)1 between 2009 and 2013. FCCA was one of the first USAID-funded projects for reducing emissions from deforestation and degradation (REDD+). The Rainforest Alliance (RA) implemented FCCA in Ghana and Honduras. Operating in two different contexts allowed FCCA to generate important lessons learned that may be useful as countries around the world search for approaches to prepare for and implement successful REDD+ mechanisms. In 2013, as FCCA was coming to an end, USAID tasked the Measuring Impact (MI) initiative with an independent review to generate lessons learned from FCCA. In capturing and disseminating lessons from the FCCA project, the Agency intends to contribute to the understanding of what may be effective, and under what conditions, when promoting REDD+ in conjunction with forest and agricultural product certification. MI is a five-year USAID project executed by the E3/FAB Office designed to improve the Agency’s practice of conservation by building USAID’s capacity to better design, manage, evaluate, and learn from biodiversity conservation initiatives. As such, MI was tasked with carrying out this review of lessons learned from FCCA while using RA’s general hypothesis as the basis to describe the project and its lessons.